The Role of Contextualism in Architectural Design of Museums - Tabarsa, Muhammad Ali; Naseri, Younes (Journal of History Culture and Art Research, 2017)
The early generator tool designs of architects in the design process are architectural context and design data, and they define the main approach of the design; this approach has led to extensive expressions of design options and ultimately they are followed by more successful assessment of solutions and more complete design. The study implements descriptive and historical analysis (using the data of ancient city and define a new set for reviving the identity and analyzing the new process). There is no doubt that the museum as a cultural institution in community is vital because the culture of a society is a general concept and it includes all the spiritual values of that community. Thus, culture is the heritage of every people, which is taken from his or her predecessors, and it has been changed and shifted to the next generation. Whenever a decision is taken to build a museum the preliminary basic problem that must be dealt with is choosing the location, a place with various facilities and each one of them need to be examined carefully. Now we should decide whether it should be in the downtown or in the suburb. But with the gradual speed increase and ease of use of public and private vehicles to get from one place to another, it was realized that a location of a museum in a downtown is not a priority anymore. A museum should be accessible from all parts of the city by public transport, and possibly by walking, and as much as possible they should be in the vicinity of schools, colleges, universities and libraries. Today, museums are seen as cultural centers more than past. But it should be noted that not only students visit them, but people who have different socio-economic background visit them. Visiting of museums are more likely if the museum is close and accessible, and coming these kinds of people even for spending their free time is an education hobby.